Applying a Proposed Recommendation System to Facilitate Web Search in Professional Community (International Conference on Computers in Education, 2010)
Web search has become an essential pathway to getting information which assists learners to acquire new knowledge and solve problems. However, web search is rather complex and challenging and learners may not acquire valuable information they really need. Recommendation systems are designed to facilitate learner's web search and proved to be efficient. Nevertheless, few recommendation systems have so far been developed to facilitate learners to use precise keywords in specific field. In this paper, an empirical study is developed to evaluate whether a proposed recommendation system can facilitate learners in professional community to use keywords precisely.